A comparative approach between different optimize result in hybrid energy system using HOMER - Shweta Goyal; Sachin Mishra; Anamika Bhatia (Institute of Advanced Engineering and Science, 2019)
To compare the different result of optimization of a hybrid energy system. A hybrid renewable energy system (HRES) is the combination of renewable and non-renewable sources which is playing a very important role for rural area electrification when grid extension is not possible or excessively expensive. Non renewable sources like diesel power generator (optional) are used in a HRES for backup when renewable energy supply is not sufficient. While the HRES is very important due to the smallest natural and physical contact compared to non renewable sources, this work proposed a comparison outcome with the help of different component by using HOMER software and get best optimize result for the model. This paper presents a wide-ranging review of various aspects of HRES. This paper discusses study, best sizing, and model, organize aspect and reliability issue.